Tingkatan Mutu dan Mitigasi Risiko pada Penanganan Udang Windu di PPI Selili Samarinda ke Pasar Barong Tongkok, Melak - Pratama, Andri; Mustaruddin, Mustaruddin; Purwangka, Fis (Jurnal Ilmu Pertanian Indonesia, 2024)
East Kalimantan has a superior commodity: tiger shrimp (Penaeus monodon). Some of these commodities are marketed to several areas in Samarinda City and to areas outside Samarinda City, namely West Kutai Regency (Barong Tongkok Market). The distribution process uses a cold chain (cool box) system for 12 hours of travel. Long distribution times cause product quality to decrease. This study aims to assess tiger shrimp’s quality and handling strategies using a cold chain system at PPI Selili Samarinda City. The quality level is determined using organoleptic testing at points 1 (PPI Selili) and 2 (Pasar Barong Tongkok). The formal safety assessment (FSA) method is used to identify risks in each handling activity, risk assessment associated with tiger shrimp deterioration, risk control, and recommendations to minimize quality degradation. Based on organoleptic tests, the quality of tiger shrimp is included in the category of safe for consumption. Product handling activities included unloading products from ships, moving them to terminals, washing, structuring, packaging in cool boxes, transportation by shipping services, shipping to Melak Pasar Barong Tongkok, unloading from shipping services, and product arrangement. The highest potential risk is handling shipments to Melak Pasar Barong Tongkok, which has 22 potential hazards. Risk mitigation can be applied through socialization and evaluation related to suitable fish handling methods (CPIB) and making operational schedules for cleaning in the product loading and unloading area before and after handling activities. Keywords: formal safety assessment, risk management, handling strategy, transportation, tiger shrimp